Análise geoespacial da Comunidade Quilombola Abacatal, Ananindeua, Pará - OLIVEIRA, Igor Klisman de Monteiro (2024)
The Comunidade Quilombola Abacatal is the closest quilombo remnant to the capital of the state of Pará, Belém. For many years, the population of Abacatal has faced conflict for the recognition of their lands as an environmental conservation unit. Without legal protection, the community had its territory inserted into the metropolitan expansion of the capita, and its lands underwent great tensions due to soil exploitation by companies. With this in mind, this work aimed to detect possible changes occurring in the soil cover in the community, aiming to identify the relationships between the processes of landscape evolution and community organization in the face of the environmental impacts generated. For this, an analysis of land cover was conducted using data from the Geographic Information System. Furthermore, we sought to understand, through a questionnaire applied in the community, the changes in the socioeconomic and cultural condition of the community after environmental changes. The results show notable changes in the community's landscape and surroundings over a period of 32 years, such as the loss of natural vegetation cover that gave way to anthropized areas. The survey instrument showed, among other things, that the quilombolas' source of income essentially went from family farming to formal jobs in the city. It is concluded that the various human actions were vectors of intense changes in the territory of Abacatal, which generated various environmental, socioeconomic and health damages for those who live in the community. The reflections presented constitute important elements for understanding and future planning of environmental conservation projects at APA Belém and UC of Abacatal.